Phase relations in Bi-rich part of the Bi-Ga-Ni system - Živković D.; Manasijević D.; Balanović Lj.; Minić D.; Ćosović V.; Kostov A.; Živković Ž. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The results of phase relations investigation in bismuth-rich part of ternary Bi-Ga-Ni system are presented in this paper. Two sections with constant bismuth content equal to 80 and 90 at% were investigated experimentally using DSC and SEM-EDS methods and predicted thermodynamically by CALPHAD method. Calculated phase diagrams showed reasonable agreement with experimental data. [Projekat Ministarstva nauke Republike Srbije, br. OI172037]